PEMETAAN SEBARAN DAN KEDALAMAN LAPISAN BATUAN AKIFER MENGGUNAKAN METODE GEOLISTRIK - Sriyono Sriyono; Dewi Liesnoor Setyowati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
Geo-electric forecase was one of geo-physic methodology that developed to determine the structural geometry of hard-rock aquifers. Some geo-electic invertigations, added to the first mapping at the local scale, and second one, this method was to lead to the building of a local geometrical model of the aquifer. A geo-electric survey, composed of vertical electrical soundings, was conducted over Banaran Regency, the part of Sekaran an Gunungpati district. Generally, the approach figurate that Banaran Regency has two characteristic of the groundwaterflow system profile. The first profile set on BAN-4 and BAN-2, show the confining aquifers, on the depth of 0-45 meter under surface, non-permanent character, shape. While the second one were set on BAN-1,3,5,6,7 on the depth of 47 meter, show the shape of, cistern, and impermeable rocks. Beside that, we found under watertable on the depth of more than 60 meter and permanent-aquifer form.